2014
DOI: 10.1007/s00348-014-1831-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flow measurements on flapping wings using synthetic aperture PIV

Abstract: We present the results of 3D velocity measurements of the flow fields around a free-flying painted lady butterfly (Vanessa cardui) and a tethered mechanical flapper using Synthetic Aperture PIV (SAPIV). The velocity fields presented for the free-flying butterfly have limited spatial resolution; however, leading edge vortices (LEV) and trailing edge vortices (TEV) can be seen during the downstroke of the butterfly. The results show that SAPIV has potential as a flow analysis tool to obtain whole-field, time-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Extensive experiments have been carried out in the past to characterize the aerodynamics of natural fliers, such as birds (Spedding et al 2003;Hedenström et al 2006;Johansson and Hedenström 2009;Cheng et al 2016), bats Hubel et al 2010;Muijres et al 2011) and insects (Ellington et al 1996;Srygley and Thomas 2002;Bomphrey et al 2006Bomphrey et al , 2012Fuchiwaki et al 2013;Muijres et al 2014;Langley et al 2014;Henningsson et al 2015). Similar studies have also been reported for flapping-wing MAVs (De Clercq et al 2009;Mazaheri and Ebrahimi 2011;Ren et al 2013), or simplified mechanisms that mimic flapping kinematics, but do not possess the ability to fly independently (Ellington et al 1996;Birch and Dickinson 2001;Lehmann et al 2005;Tarascio et al 2005;Lu and Shen 2008;Ghosh et al 2012;Cheng et al 2014;Langley et al 2014).…”
Section: Introductionmentioning
confidence: 82%
“…Extensive experiments have been carried out in the past to characterize the aerodynamics of natural fliers, such as birds (Spedding et al 2003;Hedenström et al 2006;Johansson and Hedenström 2009;Cheng et al 2016), bats Hubel et al 2010;Muijres et al 2011) and insects (Ellington et al 1996;Srygley and Thomas 2002;Bomphrey et al 2006Bomphrey et al , 2012Fuchiwaki et al 2013;Muijres et al 2014;Langley et al 2014;Henningsson et al 2015). Similar studies have also been reported for flapping-wing MAVs (De Clercq et al 2009;Mazaheri and Ebrahimi 2011;Ren et al 2013), or simplified mechanisms that mimic flapping kinematics, but do not possess the ability to fly independently (Ellington et al 1996;Birch and Dickinson 2001;Lehmann et al 2005;Tarascio et al 2005;Lu and Shen 2008;Ghosh et al 2012;Cheng et al 2014;Langley et al 2014).…”
Section: Introductionmentioning
confidence: 82%
“…The line integral method for circulation is chosen since the method of integration of all vorticity in a set area above a threshold level (e.g., Epps and Techet 2007) is extremely sensitive to the chosen threshold level. Langley et al (2014) show that the circulation magnitude is substantially underestimated at higher threshold levels even though the vorticity threshold level does not influence general temporal trends in vortex circulation as measured in a SAPIV experiment.…”
Section: Velocity Field Reconstruction and Analysismentioning
confidence: 91%
“…SAPIV methods are presented in detail by Belden et al (2010), and applications of SAPIV to flapping wings are presented by Langley et al (2014). SAPIV uses arrays of cameras, each with a different line of sight, to image a scene from multiple viewpoints.…”
Section: Synthetic Aperture Pivmentioning
confidence: 98%
See 2 more Smart Citations